Вплив типу конституції корів української чорно-рябої молочної породи на їх продуктивні якості - Карлова, Ліна Валентинівна; Karlova, L. V.; Karlova, L.; Karlova, Lina V.; Karlova, Lina Valentinovna; Karlova, Lina Valentunivna; Karlova, Lina; Іжболдіна, Олена Олександрівна; Izhboldina, O. O.; Izhboldina, O.; Izhboldina, Е. А.; Izhboldina, Н.; et al. (Вінницький НАУ, 2019)
Оцінено вплив типу конституції корів української чорно-рябої молочної породи на їх подальшу молочну продуктивність та відтворювальну здатність. Корови широкотілого типу вірогідно переважали одновікових аналогів вузькотілого типу за індексами широкогрудості та широкозадості відповідно на 2,75 (11,2%; Р>0,999) і 1,35 (5,04%; Р>0,99), величиною та напрямком відхилення. Модельне відхилення для тварин широкотілого та вузькотілого типів склало +8,77 та -6,32 відповідно. Первістки широкотілого типу вірогідно (Р>0,95) перевершують ровесниць вузькотілого типу за надоєм та кількістю молочного жиру – на 9,8 і 10,1 % відповідно. У тварин широкотілого типу на 37,8 (25,5%; Р>0,95) днів меншою була середня тривалість сервіс-періоду порівняно з вузькотілими однолітками. Вищий на 0,01 (0,9%) коефіцієнт продуктивного використання свідчить про те, що з підвищенням продуктивності у корів широкотілого типу не спостерігається погіршення відтворювальної здатності. Між типами конституції існує досить високий рівень відмінностей за показниками відтворювальної здатності, однак за живою масою різниця була незначною і знаходилася в межах (1,0%). The influence of the constitution type of cows of Ukrainian black-and-white milk breed on their further milk production and reproductive ability is estimated. Broad-cow-type cows probably prevailed for single-age analogs of narrow-necked type in terms of broad-hemisphere and broad-end indexes, respectively, at 2.75 (11.2%; P>0.999) and 1.35 (5.04%; P>0.99), magnitude and direction of deviation . The model deviation for widespread and narrow-necked animals was +8.77 and -6.32, respectively. According to the main linear measurements of the first-born of a broad-leaved type of constitution, the prevailing predominance of their peers was narrow-cut type: the height at the withers was 0.9%, the depth of the breast – 7.6%, the width of the breast – 8.5%, the width of the maclaques - 8.7 %, the oblique body length is 10.1%, the chest sheath is 3.2%, and the hemline is 1.6%. The difference in coefficient of relative decline of growth to the annual age between animals of different constitutional types is revealed. They are higher in individuals belonging to broadleaved (84,1 ± 1,89) and lower in peer group (81,2±1,43) type. This indicates that the former were formed faster and better adapted to the conditions of the environment. The first-born of the widespread type is likely (P>0.95) to exceed the age-olds of the narrow-necked type by their diet and the amount of milk fat – by 9.8 and 10.1% respectively. In broad-leaved animals, the average duration of service-period was 37.8 (25.5%; P>0.95) days less than that of narrow-necked peers. The higher the productivity factor of 0,01 (0,9%) indicates that with the increase in productivity in broad-leaved cows there is no deterioration in reproductive capacity. Between the types of constitution there is a rather high level of differences in reproductive capacity, but the difference in living weight was insignificant and was within the range (1.0%). In animals of the first type of connection with increased intake, the content of fat in milk increases, in the second – the increase in diets is accompanied by a decrease in fatty milk, in the third, when the amount of fat is removed, the fat content remains at the same level. The most valuable animals should be considered the first type. The number of such animals among broadleaved cows is 11.8% compared with the narrow-necked (11.1%). This allows selection of animals of the desirable constitutional type, which combines high productive and fat-dairy qualities. All this allows us to conclude that it is expedient to carry out the selection of animals of the desired constitutional type, which would combine high productive and reproductive qualities.
Influence of type of constitution of ukrainian black and wheat dairy breeds on their productivity quality
Карлова Ліна Валентинівна https://orcid.org/0000-0001-8213-8588 Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228 Лесновська Олена Володимирівна https://orcid.org/0000-0002-9027-6734
Keywords: проміри; measurements; первістки; first-born; широкотілий тип; broad-leaved type; вузькотілий тип; narrow-necked type; молочна продуктивність; milk productivity; відтворна здатність; reproductive ability; індекси; indices